KNOTTED1-LIKE HOMEOBOX 3: a new regulator of symbiotic nodule development - Azarakhsh, M; Kirienko, A N; Zhukov, V A; Lebedeva, M A; Dolgikh, E A; Lutova, L A (Journal of experimental botany, 2015)
KNOX transcription factors (TFs) regulate different aspects of plant development essentially through their effects on phytohormone metabolism. In particular, KNOX TF SHOOTMERISTEMLESS activates the cytokinin biosynthesis ISOPENTENYL TRANSFERASE (IPT) genes in the shoot apical meristem. However, the role of KNOX TFs in symbiotic nodule development and their possible effects on phytohormone metabolism during nodulation have not been studied to date. Cytokinin is a well-known regulator of nodule development, playing the key role in the regulation of cell division during nodule primordium formation. Recently, the activation of IPT genes was shown to take place during nodulation. Therefore, it was hypothesized that KNOX TFs may regulate nodule development and activate cytokinin biosynthesis upon nodulation. This study analysed the expression of different KNOX genes in Medicago truncatula Gaertn. and Pisum sativum L. Among them, the KNOX3 gene was upregulated in response to rhizobial inoculation in both species. pKNOX3::GUS activity was observed in developing nodule primordium. KNOX3 ectopic expression caused the formation of nodule-like structures on transgenic root without bacterial inoculation, a phenotype similar to one described previously for legumes with constitutive activation of the cytokinin receptor. Furthermore, in transgenic roots with MtKNOX3 knockdown, downregulation of A-type cytokinin response genes was found, as well as the MtIPT3 and LONELYGUY2 (MtLOG2) gene being involved in cytokinin activation. Taken together, these findings suggest that KNOX3 gene is involved in symbiotic nodule development and may regulate cytokinin biosynthesis/activation upon nodule development in legume plants.